The Effects of N-Acetylcysteine as Adjuvant Therapy To Reduce TNF-Î‘ Level And Increase SPO2/FIO2 Ratio In Improving Hypoxemia In COVID-19 Patients - Ramadhan, Fitratul; Putra, Ngakan Putu Parsama; Setyawan, Ungky Agus; Djajalaksana, Susanthy; Listyoko, Aditya Sri; Al Rasyid, Harun (Indonesian Journal of Tropical and Infectious Disease, 2021)
Tumor Necrosis Factor Alpha (TNF-α) is a pro-inflammatory cytokine that plays a crucial role in COVID-19 disease progression. N-acetylcysteine (NAC) works throughout several GSH-mediated mechanisms and is known to eliminate oxidative stress in acute respiratory distress syndrome (ARDS) in COVID-19. This study aims to analyze the effect of the N-Acetylcysteine as Adjuvant Therapy to reduce TNF-α levels and Increase SpO2/FiO2 ratio in Improving hypoxemia in COVID-19 Patients. This is a quasi-experimental, non-equivalent control group design study. There were 91 subjects selected using non-random sampling, which consisted of 75 patients in the NAC group and 16 patients in the control group. The TNF-α level was measured using the ELISA method, and SpO2/FiO2 ratio was calculated on day 1 (on admission) and day eight after NAC 5000mg/ 72 hours was given. Statistical analysis was conducted using Wilcoxon and Mann-Whitney U Test. There is a significant decrease in TNF-α level in the treatment group (median 1.49±5.22) (p=0.016) compared with the control group (median 1.64±1.99) (p=0.005). The Median SpO2/FiO2 ratio on day 1 is 163.70±69.64 in the control group and 121.49±40.41 in the treatment group (p=0.005). The Median SpO2/FiO2 ratio on day 8 is 249.69±132.26 in the control group and 151.29±59.18 in the treatment group (p=0.001). There is a positive correlation between serum TNF-α level and SpO2/FiO2 ratio after administration of adjuvant therapy NAC (r=0.240, p=0.038). There is a positive correlation and significant decrease of serum TNF-α and SpO2/FiO2 ratio after adjuvant NAC therapy, which improves hypoxemia in COVID-19 patients.